Texts in black and white: co-constructing racialised identities in post-apartheid South Africa - Gartushka, Itai (University of Cape Town, 2020)
This thesis poses the following question: are post-apartheid racialised identities constructed relationally? More specifically, this thesis investigates the co-construction of black and white racialised identities within the realm of South African public discourse. To this aim, it draws on editorials and letters to the editor which appeared in the City Press and the Sunday Times newspapers from 1994 to 2011. Informed by Foucauldian Discourse Analysis, the analysis focuses on the relationality between blackness and whiteness through a consideration of two major discourses. These discourses, labelled Bold New Blackness and Enduring Whiteness, are presented as templates for post-apartheid racialised identity construction. The analysis is comprised of three interrelated parts. The first part demonstrates that the respective templates construct racialised identities in terms of oppositional views regarding the apartheid past and the emerging post-apartheid future. Nevertheless, as each template contains references to the racialised other, it is suggested that racialised identity is co-constructed independently within each template. The second part shows that the way in which blacks and whites are positioned is constructed through constant reference across the two oppositional templates. In turn, it is suggested that racialised identity is co-constructed interdependently between the templates via an endless cycle of opposition. The third part delves into black and white subjectivities, revealing that the templates are neither wholly independent nor wholly interdependent. Instead, it is suggested that racialised identity is co-constructed through a set of entanglements, disentanglements and re-entanglements between blackness and whiteness. In this way, the thesis elucidates the post-apartheid tensions and complexities that exist around black and white racialised identity co-construction. Moreover, given that the vast majority of existing studies have presented black and white racialised identities as independent constructions to be examined separately within the respective fields of blackness and whiteness studies, this thesis highlights the fruitfulness of simultaneously utilising these otherwise disparate fields of study.